Application of Soft Computing, Machine Learning, Deep Learning and Optimizations in Geoengineering and Geoscience - Zhang, Wengang; Zhang, Yanmei; Gu, Xin.; Wu, Chongzhi; Han, Liang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book summarizes the application of soft computing techniques, machine learning approaches, deep learning algorithms and optimization techniques in geoengineering including tunnelling, excavation, pipelines, etc. and geoscience including the geohazards, rock and soil properties, etc. The book features state-of-the-art studies on use of SC,ML,DL and optimizations in Geoengineering and Geoscience. Considering these points and understanding, this book will be compiled with highly focussed chapters that will discuss the application of SC,ML,DL and optimizations in Geoengineering and Geoscience. Target audience: (1) Students of UG, PG, and Research Scholars: Several applications of SC,ML,DL and optimizations in Geoengineering and Geoscience can help students to enhance their knowledge in this domain. (2) Industry Personnel and Practitioner: Practitioners from different fields can be able to implement standard and advanced SC,ML,DL and optimizations for solving critical problems of civil engineering.
Introduction -- Methods -- Applications -- Future Applications.
Keywords: Engineering geology; Artificial intelligence; Civil engineering; Geoengineering; Artificial Intelligence; Civil Engineering; Earth sciences -- Data processing; Geotechnical engineering -- Data processing; Machine learning; Soft computing